Audience Competency in Romans and Paul’s Flexible Use of Scripture - B. J. Oropeza (Religions, 2021)
A phenomenon noticeable in many of Paul’s quotations of Scripture is the way that they do not follow the texts he cites verbatim. This prompts the question as to whether his audience would be competent enough to detect these differences. This study considers aspects such as text variations, memory, notetaking, and rhetorical argument as potential factors related to Paul’s flexible use of Scripture in Romans. The study then probes whether Paul’s audience, particularly believing gentiles in Rome, would have known Jewish Scripture well enough to evaluate Paul’s use of Scripture. Through congregational longevity, plurality of audience, synagogue influence, and other factors, it is concluded that there is indeed competency among Paul’s auditors, but there is no evidence suggesting that he is concerned about their reacting negatively to the elasticity of his quotations.